Pengaruh Badan Usaha Milik Desa, Aset Desa terhadap Kesejahteraan Masyarakat melalui Pendapatan Asli Desa di Kabupaten Lampung Selatan - Deni Afero; Pitojo Budiono; Feni Rosalia (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
One of the government's efforts to improve community welfare is carried out through Village-Owned Enterprises (BumDes). This paper will measure the influence of BumDes management and Village asset management on the welfare of village communities in South Lampung Regency through Village Original Income (PADes) which is a mediating variable. This paper uses a type of causality research with a quantitative approach. The calculations in this paper use a quantitative approach with the help of the Smart PLS version 3.0 application. The results of this paper found that the management of BumDes has a significant effect on community welfare variables. These results prove the ability to improve community welfare through well-managed and cooperative BumDes management. Meanwhile, village asset management does not have a significant effect on the welfare of the village community in South Lampung Regency. Apart from that, BumDes management has a significant effect on the PADes variable, and village asset management has a significant effect on PADes. Based on these results it can be said that the better the management of village assets in South Lampung Regency, the more PADes the village has. Meanwhile, BumDes Management and Village Asset Management have a significant influence on community welfare through Village Original Income.